Naked statistics : stripping the dread from the data - Wheelan, Charles J. (New York : W.W. Norton & Company, 2013)
Demystifies the study of statistics by stripping away the technical details to examine the underlying intuition essential for understanding statistical concepts.
Introduction: Why I hated calculus but love statistics -- What's the point? -- Descriptive statistics : Who was the best baseball player of all time? -- Deceptive description : "He's got a great personality!" and other true but grossly misleading statements -- Correlation : How does Netflix know what movies I like? -- Basic probability : Don't buy the extended warranty on your $99 printer -- The Monty Hall problem -- Problems with probability : How overconfident math geeks nearly destroyed the global financial system -- The importance of data : "Garbage in, garbage out" -- The central limit theorem : The Lebron James of statistics -- Inference : Why my statistics professor thought I might have cheated -- Polling : How we know that 64 percent of Americans support the death penalty (with a sampling error (plus or minus) 3 percent) -- Regression analysis : The miracle elixir -- Common regression mistakes : The mandatory warning label -- Program evaluation : Will going to Harvard change your life? -- Conclusion : Five questions that statistics can help answer -- Appendix : Statistical software.
Includes bibliographical references (pages 261-267) and index.
Keywords: Statistics